Inner shell photofragmentation of 2Cl-pyrimidine studied by mass spectrometry and electron–ion coincidence experiments. (19th November 2020) - Bolognesi, Paola; Kettunen, Antti; O'Keeffe, Patrick; Richter, Robert; Cartoni, Antonella; Casavola, Anna Rita; Castrovilli, Mattea C; Tosic, Sanja; Marinkovic, Bratislav P; Avaldi, Lorenzo
Abstract: Photoelectron spectroscopy, mass spectrometry and electron–ion coincidence experiments combined with tunable synchrotron radiation have been used to study the decay and fragmentation of 2Cl-pyrimidine after Cl(2p), C(1s) and N(1s) excitations. The goal is to investigate how the state- and site-selected excitation and the chemical environment affect the fragmentation paths of the molecule and to make a comparison with fragmentation induced by direct valence ionization. It has been found that the site-selective inner shell excitation affects the branching ratio of the fragments, while the particular fragmentation channels of the cation are determined by the final state populated in the resonant decay of the core excited states. Effects of nuclear motion in the core excited states and the possible ultrafast molecular dissociation following the Cl(2p → σ * ) core excitation are discussed.